2011
DOI: 10.1021/jf2014149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymol on Mushroom Tyrosinase-Catalyzed Melanin Formation

Abstract: The novel inhibitory mechanism of thymol (2-isopropyl-5-methylphenol) on dopachrome formation by mushroom tyrosinase (EC 1.14.18.1) was identified. The UV-vis spectrum and oxygen consumption assays showed dopachrome formation using L-tyrosine as a substrate was suppressed by thymol. This inhibitory activity was reversed by the addition of a well-known radical scavenger, butylated hydroxyanisole (BHA). Further investigations using N-acetyl-L-tyrosine as a substrate with HPLC analysis suggested that thymol inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 23 publications
(30 reference statements)
1
47
0
Order By: Relevance
“…Thus, the suppression of the formation of dopachrome by thymol is due to inhibition of leuko-dopachrome to dopachrome conversion. The antioxidant properties of thymol are considered as a key feature to the mechanism of inhibition of melanin synthesis [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the suppression of the formation of dopachrome by thymol is due to inhibition of leuko-dopachrome to dopachrome conversion. The antioxidant properties of thymol are considered as a key feature to the mechanism of inhibition of melanin synthesis [39]. …”
Section: Resultsmentioning
confidence: 99%
“…However, Satooka and Kubo 60 reported that thymol was an important inhibitor against tyrosinase in melanogenesis. In this direction, the high level of thymol in the studied essential oil could be responsible of tyrosinase inhibitory activity of the essential oil.…”
Section: Tyrosinase Inhibitionmentioning
confidence: 99%
“…Liu (2003) and Chen (2005) also reported that alkoxy benzoic acids and hydroxy benzoic acids showed potent mushroom tyrosinase inhibitory activity [13,14]. Thymol a naturally occurring monoterpene phenol which is the main constituent of thyme possesses tyrosinase inhibitory activity [15] along with other numerous pharmacological activities. As phenolic antioxidants, thymol protects food qualities and organisms from damage induced by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%